The intervertebral joints I: The intervertebral disc - Jeanette Mitchell (AOSIS, 1991)
The structure of the intervertebral disc is described in detail, some reference being made to clinically relevant aspects of the anatomy. Some biomechanical terms, such as motion and force, creep and hysteresis, are explained and discussed in relation to the intervertebral disc as a clinically important structure.